2014
DOI: 10.1530/eje-14-0389
|View full text |Cite
|
Sign up to set email alerts
|

mTOR activation in medullary thyroid carcinoma with RAS mutation

Abstract: Objective: Rearranged during transfection (RET) mutations are well-known genetic events in sporadic and familial medullary thyroid carcinoma (FMTC). The presence of RAS mutations in sporadic cases, challenging the RET paradigm in these tumors, has been recently reported. We intend to evaluate mTOR pathway activation in RET-and RAS-mutated MTC. Materials and methods: In this study, we analysed the presence of RET, H-RAS, and K-RAS mutations in a series of 87 MTCs (82 apparently sporadic and five FMTCs; five app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…The OPN staining score (range from 0 to 7) corresponds to the sum of staining intensity and the proportion of positive-stained cells (Table 3). OPN staining score was correlated with data previously obtained by our group in this tumour series with regards to PTEN and pS6 IHC expression (25).…”
Section: Immunohistochemistrymentioning
confidence: 64%
See 2 more Smart Citations
“…The OPN staining score (range from 0 to 7) corresponds to the sum of staining intensity and the proportion of positive-stained cells (Table 3). OPN staining score was correlated with data previously obtained by our group in this tumour series with regards to PTEN and pS6 IHC expression (25).…”
Section: Immunohistochemistrymentioning
confidence: 64%
“…As higher levels of OPN were significantly associated with higher levels of nuclear PTEN in MTCs, these two molecules can probably act together in the maintenance of the differentiation of C-cells, thus contributing to prevent tumour progression. In sporadic MTC, RAS mutations are often detected in HRAS and KRAS genes (25), representing an alternative genetic event to RET mutation. Casson et al (50) showed that RAS mutation induces expression of OPN in human esophageal cancer, and other authors reported that OPN promoter have target sequences for RAS binding, inducing OPN expression in both human (51) and mouse (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be seen whether RAS mutations can also lead to the activation of both of these signaling pathways in sporadic MTC, or whether there is a preferential activation pathway. Lyra et al examined mTOR activation in a series of 87 MTCs (10 familial and 77 sporadic) and found RAS mutations significantly associated with a more intense expression of phospho-S6 ribosomal protein (p-S6, a downstream effector of mTOR) [44], pointing to an association between mTOR pathway activation and the presence of RAS mutations in MTC. We consequently conducted a recent study and demonstrated that MTC-harboring RAS mutations showed a preferential activation of the PI3K/Akt/mTOR pathway, revealed by an intense phospho-Akt reactivity pattern on Western blot analysis [24].…”
Section: Discussionmentioning
confidence: 99%
“…Also, other genetic events are determinant for the pathogenesis of MTC, as indicated by the recent findings of H-RAS mutations in 13-56% of RET-negative sporadic MTC and the activation of the mTOR intracellular signaling pathway in hereditary MTC [42][43][44].…”
Section: Molecular Pathways In Mtcmentioning
confidence: 99%